Exploring Pathways to Teacher Mental Health: A Mixed Methods Narrative Review of Job Demands, Job Resources, Professional Development, and Mediating Mechanisms in Multigrade Schools - Cuerdo, Agnes (JPAIR Institutional Research, 2026)
Teacher mental health is a global concern shaped by workload, emotional labour, and time pressure. Guided by the Job Demands-Resources (JD-R) framework, this review synthesizes evidence published between 2020 and 2025 across diverse contexts. A narrative synthesis integrated quantitative, qualitative, and mixed-methods studies addressing job demands, job resources, occupational stress, teacher self-efficacy (TSE), and professional development (PD). Elevated demands—including administrative overload, role conflict, and multigrade complexity—consistently predict stress and burnout. Conversely, resources such as supportive leadership, collegiality, autonomy, and adequate materials enhance well-being and buffer strain. PD adequacy strengthens TSE, which mediates positive mental health outcomes and improves resilience. Findings highlight that dual-channel strategies—reducing avoidable demands while strengthening resource conditions—outperform isolated resilience initiatives. System-level supports, including protected planning time, collaborative structures, and job-embedded PD, are particularly critical in multigrade schools where stacked demands intensify stress. Comparative analysis underscores regional relevance: ASEAN-based studies reveal how workload and self-efficacy directly affect well-being in resource-constrained schools, while collegial support and resilience strategies buffer adverse effects. These findings complement Western evidence and emphasize the need for localized interventions. Overall, teacher mental health emerges from the dynamic interplay of structural conditions and psychological mechanisms. Sustainable improvements require coordinated interventions that reduce unnecessary demands, cultivate resource-rich environments, and strengthen self-efficacy. By integrating global and regional perspectives, this review advances theoretical understanding of JD-R pathways while offering practical recommendations for policy and practice, particularly in low-resource and multigrade settings.
Keywords: Education; teacher mental health; job demands; job resources; self-efficacy; multigrade schools; mixed-methods